2022
DOI: 10.1007/s10639-022-11063-y
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the impact of quality elements on MOOCs continuance intention

Abstract: Online learning has captured much attention, while given for high dropout rate, continuance of MOOCs is now a most concerned critical topic in both research and practical field. From teaching-based quality and platform-based quality perspectives, this study aims to investigate the impact of quality elements on continuance intention based on Expectation Confirmation Model, Task Technology Fit, flow theory and trust. We conducted our research through online questionnaire from July to September in 2020 and collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 94 publications
4
9
1
Order By: Relevance
“…This shows that even if students have the technological and financial means to use MOOCs, learning through them is not necessarily the goal. This result is consistent with some earlier research that indicated the negligible effect of TTF on students’ use of MOOCs ( Alyoussef, 2021 ; Shanshan and Wenfei, 2022 ) and accepting behavior ( Mohan et al, 2020 ). Being Perceived Autonomy (H3) has been shown to do positively influence students’ Intrinsic Motivation, which suggests that it can improve social interaction and increase the acceptance of MOOCs.…”
Section: Discussionsupporting
confidence: 93%
“…This shows that even if students have the technological and financial means to use MOOCs, learning through them is not necessarily the goal. This result is consistent with some earlier research that indicated the negligible effect of TTF on students’ use of MOOCs ( Alyoussef, 2021 ; Shanshan and Wenfei, 2022 ) and accepting behavior ( Mohan et al, 2020 ). Being Perceived Autonomy (H3) has been shown to do positively influence students’ Intrinsic Motivation, which suggests that it can improve social interaction and increase the acceptance of MOOCs.…”
Section: Discussionsupporting
confidence: 93%
“…Many researchers combine TTF with other theories to explain students’ and teachers’ online learning behaviors ( Alyoussef, 2021 ; Kori and Pedaste, 2021 ). For example, Shanshan and Wenfei (2022) studied the impact of quality factors on the intention of continuous use of MOOCS from the perspective of quality based on teaching and platform, integrating ECM, TTF, flow theory, and trust. Wan et al (2020) surveyed the determinants of college students’ satisfaction to continue using MOOCs by integrating the unified theory of acceptance and use of technology (UTAUT), TTF, and user satisfaction.…”
Section: Research Model Literature Review and Hypothesesmentioning
confidence: 99%
“…A higher fit indicates a higher perception of ease of use. TTF has an indirect impact on the "perceived usefulness" through the "perceived ease of use" (Yen et al, 2010;Wu and Chen, 2016;Shanshan and Wenfei, 2022). This study integrates TTF into our research framework to investigate its impact on perceived usefulness and perceived ease of use.…”
Section: Hypothesesmentioning
confidence: 99%
“…In terms of the trend of research related to digital learning, most studies have concentrated on recognising the effect on learners' performance, engagement, and motivation (e.g., Zainuddin et al, 2020) as well as the acceptance of the product (e.g., Lestari & Nugraha, 2021;Md Yunus et al, 2021). Meanwhile, studies related to 'continuance use intention' on product use of e-learning (e.g., Al Amin et al, 2022), Massive Open Online Courses (MOOC) (e.g., Shanshan & Wenfei, 2022), Learning Management Systems (LMS) (e.g., Ashrafi et al, 2022;Widjaja & Widjaja, 2022) and m-learning application (e.g., Khlaif et al, 2022;Tam et al, 2020) were already done; however, studies on continuance use intention mainly on a gamified m-learning application is scarce (Roslan et al, 2021a;Wirani et al, 2022), making this a critical literature gap.…”
Section: Introductionmentioning
confidence: 99%